2022
DOI: 10.1177/08874034211065992
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology and Positive Criminology: Similarities and Differences

Abstract: The purpose of this review is to highlight the similarities and differences between positive psychology and positive criminology—both relatively new concepts that represent an optimistic view of human beings and their ability to recover—while calling for a change of focus in the discourse and research of their respective fields. To this end, we first present a brief overview of each of these perspectives, along with findings of studies that confirm their assumptions, and then address their similarities and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…We begin with a comparing and contrasting of positive criminology and positive psychology by the authors who originally proposed positive criminology . In their discussion, Elisha and Ronel (This issue) hint that, together, the two positives work to secure human thriving and optimal functioning such that people can make non-deviant choices in situations where they would have sought crime in the past. The authors then provide an overview of current research and settings where positive criminology has shown a positive impact on behaviors by allowing people to learn from their past successes and their past failures.…”
mentioning
confidence: 99%
“…We begin with a comparing and contrasting of positive criminology and positive psychology by the authors who originally proposed positive criminology . In their discussion, Elisha and Ronel (This issue) hint that, together, the two positives work to secure human thriving and optimal functioning such that people can make non-deviant choices in situations where they would have sought crime in the past. The authors then provide an overview of current research and settings where positive criminology has shown a positive impact on behaviors by allowing people to learn from their past successes and their past failures.…”
mentioning
confidence: 99%